Effect of the Roast Level on Lipophilic and Hydrophilic Compounds in Pot and Filter Coffee Beverages - Ollennu-Chuasam, Priscilla; Suomela, Jukka-Pekka; Hanhineva, Kati; Linderborg, Kaisa M.; Koistinen, Ville (American Chemical Society, 2025)
Roast levels may affect the profile and content of phytochemicals in coffee. The composition of potentially bioactive compounds was investigated in pot coffee (PC) and filter coffee (FC) beverages prepared from light, medium, medium-dark, and dark roasted coffee using UHPLC-QTOF/MS. The metabolites affected by roast level (ANOVA, p < 0.05) included deoxycarnitine, tyrosine, and sn-glycero-3-phosphocholine. Compounds such as dehydrosalsolidine, deoxycarnitine, and adenosine 3,5-cyclic monophosphate were identified in coffee for the first time. The intensities of chlorogenic acid, trigonelline, choline, and rosmarinic acid in the beverages decreased with a higher roast level. In contrast, the level of quinic acid, theobromine, and N,N-dimethylpiperidinium, a Maillard reaction product, increased. The caffeine content was relatively stable from light to dark roast, while cholesterol-elevating diterpenes decreased. This study provides information on the optimal coffee roast level for several potentially bioactive compounds and aroma precursors to maximize coffee quality, especially in terms of its potential health benefits.